2016
DOI: 10.15562/bmj.v5i2.210
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Red Piper Crocatum Leaves Extract Decrease TNF-α and IL-6 Levels in Wistar Rat with Atherosclerosis

Abstract: Background: This research aims to find a cure for anti-inflammation, based on the utilization of red piper crocatum. The research was started with descriptive study to explore active components of red piper crocatum leaf and followed by experimental study to investigate red piper crocatum activity of the leaf extract in anti-inflammation induced Wistar rat. In this research observed three dominant components: caryophyllene bicyclo [5.2.0] none, 2 methylene-4, 8,8-trimethyl-4-vinyl; phytol; 5,9-propano-5H-benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Wicaksono et al(2009) reported P. crocatum methanol extract inhibits the growth of human breasts cancer (T47D) cells via inhibition of p44/p42 phosphorylation. Recent study shows P. crocatum leaves extract to act as anti-inflammation in Wistar rats with atherosclerosis through decrease of TNF-and IL-6 levels (Wahjuni et al, 2016). Anti-inflammatory properties of P. crocatum might be correlated with compounds contained in the plants.…”
Section: Discussionmentioning
confidence: 98%
“…Wicaksono et al(2009) reported P. crocatum methanol extract inhibits the growth of human breasts cancer (T47D) cells via inhibition of p44/p42 phosphorylation. Recent study shows P. crocatum leaves extract to act as anti-inflammation in Wistar rats with atherosclerosis through decrease of TNF-and IL-6 levels (Wahjuni et al, 2016). Anti-inflammatory properties of P. crocatum might be correlated with compounds contained in the plants.…”
Section: Discussionmentioning
confidence: 98%
“…The role of endoglin in this context is of particular interest [17][18][19][20]. Macrophages play a crucial role in the development of atherosclerosis, which can be triggered by endothelial dysfunction, hypertension, vasculitis, aortic aneurysm, or other vascular disorders [21,22]. The polarization and accumulation of macrophages in a chronic pro-inflammatory state can lead to significant and irreversible vascular damage, affecting clinical outcomes [23].…”
Section: Hypoxiamentioning
confidence: 99%
“…The studies cited above report the traditional use of this species, P. aleyreanum, as immunomodulatory, analgesic and antidepressant (Brait et al, 2015); people use it empirically in a more general way for bronchitis, intestinal pain, skin irritations and inflammation treatment (Lima et al, 2012). Wahjuni et al (2016) and Laksmitawati et al (2017) performed tests with P. crocatum. Both evidenced the reduction of serum levels of TNF-α, IL-1, IL-6, and NO in Wistar rats and in LPS-induced macrophage cells, respectively.…”
Section: Leaves Dichloromethane Extractmentioning
confidence: 99%